ONLAY BLOCK BONE GRAFTING IN ALVEOLAR DISTRACTION OSTEOGENESIS TO INCREASE CALLUS VOLUME - (:unkn) unknown (NOVA SCIENCE PUBLISHERS, INC, 2010)
The functional and esthetical rehabilitation of the maxilla with dental implants when there is a severe alveolar bone deficiency can be achieved with the help of distraction osteogenesis. Although this method offers certain advantages over conventional augmentation methods, it sometimes requires secondary bone grafting because the bone of the transport segment may be too thin and semilunar excavations may form in the distraction zone. In this situation, the simultaneous application of distraction osteogenesis with a polytetrafluoroethylene membrane and autogenous onlay block bone grafting is an alternative solution to secondary bone grafting. In addition, this technique prevents semilunar excavations in the distraction zone and increases callus volume.
Keywords: RIDGE AUGMENTATION; IMPLANT PLACEMENT; CLINICAL REPORT; RECONSTRUCTION; MEMBRANE; DEFECTS